Kinetics Study of Fe Content Decrease In Well Water With Activated Carbon Adsorption Of Coffee Waste - Adi Prima Rizki (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Water wells that contain iron will cause harm to living organisms, especially humans. Experiment of Fe adsorption on well water using activated carbon. On the experiment, coffee waste used as materials for making charcoal, activated charcoal is subsequently used to reduce Fe. Adsorption of Fe at 400 rpm achieved optimum contact time of 20 minutes. While at 500 rpm achieve optimum value at 15 min and 600 rpm achieve optimum at 25 minutes. Isothermal adsorption model is isothermal Langmuir with R2 for 400 rpm and 500 rpm are 0,999 and for 600 rpm is 0.996. Langmuir equation shows the rate of 400 rpm has the best adsorption capability with a value is 1,267. Fe adsorption with activated charcoal from coffee waste at a rate of 400 rpm to adequate the kinetics model of order 0, whereas the rate of 500 and 600 rpm adequate the second-order kinetic.